1984
DOI: 10.1007/bf00495770
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 35S-taurine in rat neonates and adults

Abstract: The distribution of 35S-taurine in rat neonates and adults was investigated by wholy -body autoradiography. The neonates (4-day-old) were frozen in dry-ice hexane at 30 min, 1, 3 and 6 h after an intraperitoneal injection of 35S-taurine, whereas survival intervals for adult rats were 1 and 3 h. Whole-sagittal sections of the frozen rat, obtained by using a cryostat microtome were dried in situ and autoradiographed. In rat neonates and adults, 35S-taurine was mainly accumulated in the renal cortex, urine, feces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…At high magnification, we found that the living cells have two kinds of verruciform protrusions on the cell surface. In the previous study, we reported the ultrastructural observation of Cbattone/& antiqua and observed some mucocysts protruding from the cell membrane (Shimada et al, 1986). Therefore, it is conceivable that the verruciform protrusions seen in the present work might be the heads of mucocysts located in the glycocalyx (Yokote and Honjo, 1985).…”
Section: Discussionsupporting
confidence: 53%
“…At high magnification, we found that the living cells have two kinds of verruciform protrusions on the cell surface. In the previous study, we reported the ultrastructural observation of Cbattone/& antiqua and observed some mucocysts protruding from the cell membrane (Shimada et al, 1986). Therefore, it is conceivable that the verruciform protrusions seen in the present work might be the heads of mucocysts located in the glycocalyx (Yokote and Honjo, 1985).…”
Section: Discussionsupporting
confidence: 53%
“…In the hypophysis and pineal gland, the transporters involved are also unknown. The presence of very high radioactivity in the hypophysis and pineal gland after 14 C-GABA injection is of particular interest since taurine, which is structurally related to GABA, also strongly incorporates into these organs (Shimada et al, 1984). The functional relationship between taurine and GABA has been reviewed elsewhere (Huxtable, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated whether KCC2 may be inhibited by undefined embryonic factors. Taurine is a candidate due to enrichment in immature neurons during cerebral cortex development (30,31). In addition, taurine-deficient kittens show abnormal neuronal migration in the cerebral cortex and cerebellum (32,33).…”
mentioning
confidence: 99%